Investigations of specialised metabolites of endophyte Diaporthe destruens hosted in Illigera orbiculata C. Y. Wu. (November 2022) - Zhang, Sheng-Qi; Wang, Jia-Peng; Zhang, Feng-Mei; Yao, Lin-Lin; Li, Bing-Xian; Li, Ya-Ni; Gan, Dong; Mei, Rui-Feng; Cai, Le; Ding, Zhong-Tao
Abstract: A chemical investigation of the endophytic fungus Diaporthe destruens from the Hernandiaceae plant Illigera orbiculata C. Y. Wu collected from southern Yunnan Province, China, led to the isolation of six undescribed compounds, including two azaphilone analogs, which are a pair of epimers (13 R- hydroxy-chermesinone A and 13 S- hydroxy-chermesinone A); a pyrrole derivative (1-(4-(methoxymethyl)-1H-pyrrol-3-yl)ethan-1-one); an isoindolone derivative (4-hydroxy-6-methoxyisoindolin-1-one); a benzylbenzene derivative (destruensine A) and a conjectural fragment of polyketide ((2 R, 4 R )-2-(methoxymethyl)pentane-1, 4-diol) along with nine known compounds. Their structures were elucidated by spectroscopic methods and HRESIMS, and the absolute configurations were further confirmed by electronic circular dichroism (ECD) and chemical derivatization. The antimicrobial activities, anti-acetylcholinesterase activities, antiproliferation, and NO production inhibitory effects of compounds 1 –15 were evaluated. Graphical abstract: Fifteen specialised products, including six undescribed structures, were obtained from Diaporthe destruens hosted in Illigera orbiculata . Their bioactivities were evaluated. Image 1 Highlights: Six undescribed compounds were isolated from the fungus Diaporthe destruens. The absolute configurations of the undescribed compounds were established. The bioactivities of the isolated compounds were evaluated.